Epistemologi Pendidikan: Elaborasi Pengetahuan untuk Mencapai Keautentisitasan Kecerdasan Manusia - Jatmika, Bayu Jati; Amalia, Kiki (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
The fundamental question in educational philosophy that is in line with the goals of education is the question of why humans must be educated and what goals must be achieved in the educational process. In a different sense, educational epistemology concerns the issue of how we arrive at knowledge about educational problems. The main issues and ideas of epistemology are; a) what is knowledge? b) what is the best and safest way to gain knowledge? c) what is the value of knowledge? One of the goals of epistemology is to determine the criteria for knowledge so that we can know what can or cannot be known, in other words the study of epistemology basically includes the study of meta-epistemology (what we can know about knowledge itself). The nature of knowledge centers on the question "how" we know what we know, what makes us believe that something is "true". Epistemology is not just about acquiring knowledge but also about understanding the process of acquiring knowledge. Thus the real question is "with what should education begin?" and "with what knowledge should knowledge about education begin?".